An Empirical Analysis of Welfare Dependence in the Czech Republic - Martin Guzi (Institute for the Study of Labor (IZA), 2013)
Paper demonstrates the existence of a welfare trap in the Czech Republic, created by the tax and social security systems. Combining individual data from the Czech Labor Force Survey and the Czech Household Income Survey, the analysis exploits the difference between the available social benefits and the net household income when a person is employed. This information allows us to calculate the net replacement rate based on the parameters of the taxation system and rules for means-tested social benefits at the household level. Estimates imply the existence of a welfare trap, which means that individuals who receive relatively higher social benefits are also more likely to remain unemployed. It is shown that the most affected groups are those with low education and long unemployment spells. Furthermore, the paper documents the disadvantaged position of women in the Czech labor market. The estimates imply that women outflows to employment are particularly influenced by the high social benefits, and the existence of a welfare trap persists even when the job-search intensity is controlled. This finding contributes to the discussion on the persistent and large unemployment gender gap in the Czech Republic. The results of the analysis support policy improvements towards low-income households. A better harmonization of tax and social security systems is necessary in order to ensure that the incentives to leave unemployment are not hampered by high social benefits.
Keywords: J22; J31; I38; 330; labour supply; welfare trap; net replacement rate